Renal fascia in normal and ectopic pelvic kidneys: Evidence-based clinical and anatomical review - Kalpana Ramachandran; Sriram Krishnamoorthy (Wolters Kluwer Medknow Publications, 2021)
The natural location of the kidney is the loin and the fascial sheaths around it gives it inherent protection against trauma and various other diseases. While there is enough evidence for fascia around well ascended normally located kidneys, there is very little evidence for its presence in ectopic pelvic kidneys. This evidence-based review discusses the recent changes in concepts regarding renal and perirenal fascia in normal and ectopic kidneys. The perirenal fascia was described as anterior and posterior layers that fuse laterally to form the lateral conal fascia. However, subsequent studies have shown that these fasciae are multi-laminated structures that blend and fuse with underlying muscles. However, in pelvic kidneys, the anterior and posterior renal fascia is not so well-documented. The medial extension of the enlarged kidney enables an easy cross-over to the opposite side. A subcapsular urinoma or a perirenal hematoma is usually self-contained in a closed space, owing to the attachments of the renal capsule and the perirenal fasciae. The hematoma in such closed space acts as a self-tamponade, preventing further blood loss or hemodynamic instability. Computed tomography has enhanced the understanding of perirenal space and pathologies. Tri-compartmental theory formed the basis for a clear understanding of these fasciae. A better knowledge of these fascial planes helps the surgeons to identify the avascular planes, better. A larger prospective study is needed to get further insights into renal fascia in pelvic kidneys.